Sistemas de ejercicios para el desarrollo de la fuerza en el tren inferior de los jugadores de fútbol del club deportivo “París” de la categoría Sub 18, del cantón Vinces - 2021 - Mina Calberto, Kimberly Noheli (2021)
Force is an ability of muscle segments to generate tension under specific conditions. In football there are many demands such as jumps, they are used to perform shots, passes, serves and controls. Strength is also required in the different displacements that are given to make changes of directions, races and changes of pace. That is why force plays an important role in football. For the development of this work, a non-experimental design research was applied, with a descriptive cross-section, with a population of 20 soccer players from the Club Deportivo Paris in the sub-18 category and 2 coaches, surveys were applied to determine the level of knowledge they had about aspects of soccer training. Physical tests were applied to the players to assess their strength levels. After carrying out the proper analysis and interpretation of the data, the results were that both as coaches and players if they consider the development of lower body strength to be important in their career as a footballer. In the physical tests it was evidenced that there are players who have low levels of strength, but the one that showed the most was explosive-type strength. Thus, a proposal of exercise systems will be proposed to develop the explosive strength of the lower body of the players of the Club Deportivo Paris, in the sub 18 category of the Vinces canton.